Muslim Science Thought from The Perspective of Abu Bakr Muhammad Zakariya ar-Razi - Unzilatun Nikmah; Mawaddatul Jannah (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2024)
Many prominent and renowned philosophers and scientists in their respective fields were born by the Islamic civilization. With his book Al-Hawi fi al-Ṭibb, al-Razi, one of the Islamic scholars, had a great influence in the world of science. Although he adhered to the theocentric and anthropocentric paradigms, he rejected the "prophetic understanding", which caused great problems and accusations of being al-mulḥid (atheist). This study aims to fulfill the author's desire to know and investigate the origins of the idea, al-Razi's perspective on the integration of religion and science, especially in the field of medicine, and its influence on the progress of science today, especially in the field of health and medicine. Data were taken from reference books and scientific journals. The data collection method used reading, note-taking, and document analysis. Data analysis was conducted through three stages: data reduction, data presentation, and conclusion. The results of the research on his thoughts on prophethood and revelation are problematic but do not eliminate the divine nuances in his work in the field of medicine, the tendency towards communication and integration, where science and religion have the same goal, that Ar-Razi's work and treatment techniques contribute to modern society.